PENATALAKSANAAN PEMERIKSAAN TRIPEL ELIMINASI PADA IBU HAMIL DI PUSKESMAS TANJUNG BALAI KARIMUN - Muti Qurnia; Prasida Yunita; Nova Roza (Universitas Batam, 2023)
WHO (World Health Organization) explained that in 2016 Asia accounted for around 50% of cases of STIs (Sexually Transmitted Infections). The prevalence of HIV infection, syphilis and hepatitis B in pregnant women in Indonesia is 0.3%, 1.7% and 2.5% respectively. The screening test for HBsAg, HIV and Syphilis is called Triple Elimination. Research objectives Provide midwifery care related to basic clinical skills regarding the management of sexually transmitted infection screening in pregnant women by carrying out triple elimination. The type of research used in the preparation of practice reports is descriptive research using the case study method. The research was conducted at the Tanjung Balai Karimun Health Center in January 2023. The subject used in this case study with midwifery care management was Mrs. H, pregnant women at high risk. The implementation of the triple elimination program is also very effective in preventing the transmission of HIV, Hepatitis B and Syphilis from mother to baby.